2010
DOI: 10.1007/s12028-010-9336-3
|View full text |Cite
|
Sign up to set email alerts
|

Slippery Platelet Syndromes in Subdural Hematoma

Abstract: Platelet dysfunction was found in 38% of SDH patients. This finding adds to our understanding of the pathophysiology of SDH. Since platelet transfusions are indicated for platelet dysfunction accompanied by major bleeding or need for surgery, these results impact peri-operative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(33 reference statements)
1
4
0
1
Order By: Relevance
“…This corresponds well with previous reports of TEG-PM demonstrating reduced platelet activity in patients with TBI [45]. PFA-100 was used in 58 patients with subdural haematoma and 38% of these patients had impaired platelet function [46]. The PFA-100 was also used as a screening tool prior to elective neurosurgical procedures by Karger and colleagues who found that 15 out of 93 patients had abnormal findings [47].…”
Section: Assessment Of Platelet Functionsupporting
confidence: 86%
“…This corresponds well with previous reports of TEG-PM demonstrating reduced platelet activity in patients with TBI [45]. PFA-100 was used in 58 patients with subdural haematoma and 38% of these patients had impaired platelet function [46]. The PFA-100 was also used as a screening tool prior to elective neurosurgical procedures by Karger and colleagues who found that 15 out of 93 patients had abnormal findings [47].…”
Section: Assessment Of Platelet Functionsupporting
confidence: 86%
“…In a pilot study, the degree of hematoma evacuation was !90%, 75 to 89% and 50 to 74% in 74, 20, and 5.7% of patients, respectively, with an overall 3% rebleed rate. There were reported improvements in preoperative to postoperative GCS scores (10)(11)(12)(13). 90 This device seems to be used predominantly in a lobar location.…”
Section: Surgical Managementmentioning
confidence: 98%
“…There is increasing evidence that ICH is complicated by impaired platelet function, most often as a result of antiplatelet agent (APA) ingestion, although other etiologies may exist. [10][11][12][13] As a result, platelet function is increasingly evaluated and platelet transfusions are often given in the setting of acute spontaneous ICH in an effort to promote hemostasis. There is little evidence currently to guide this practice.…”
Section: Introductionmentioning
confidence: 99%
“…Bereits 2010 wurde eine interessante Arbeit publiziert, die an 58 Patienten mit SDH eine Thrombozytenfunktionsdiagnostik mittels des PFA-100 vornahm [57]. Bei 40 % (n = 6) der Patienten, die mit VKA behandelt waren, konnte zusätzlich eine Thrombozytenfunktionsstörung nachgewiesen werden.…”
Section: Merkeunclassified